Heterogeneity of the impact of scholarships in Spain in the upper secondary education: a sub-population analysis - Mediavilla, Mauro (Estudios de Economía, 2013)
The main objective of this study is to identify and quantify the existence of an impact on upper secondary completion rates of a scholarships program applied to different sub-populations in Spain. The evaluation is performed applying an ex-post quasi-experimental approach technique, the propensity score matching, to microdata obtained from the European Union Statistics on Income and Living Conditions (EU-SILC 2006). Results confirm the existence of a differential positive effect of scholarships for women and students from disadvantaged households, demonstrating the existence of heterogeneous impacts of the policy analysed.